(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Essential oils (EOs) are potential alternatives to conventional pesticides, among plant extracts used as insecticides. EOs are generated by plants and play a significant function in plant signaling, including the appeal for pollinators and beneficial insects Plant species that produce essential oils are referred to as aromatic plants and dispersed over the globe. Our study seeks to analyze research publications on usage of EOs in stored product protection published during the past 15 years, examining diverse elements of insect pest control. Study on insect pests of stored grain, Damage, essential oils on insect pests Process Effectiveness of essential oils as insect control fumigants for stored product insects, Mode of action of essential oils possible, ESSENTIAL EARLY MODE OF ACTION, Checking insect pests stored in grain, Physical methods for the control of stored grain, Control and their negative effects of stored grain using chemical pesticides, Natural products control of stored grain, Preservation of laboratory insect culture.